(untitled) (Jurnal Kemanusiaan, 2017)
Exclamation sentence is a style using in the Quran. In Arabic, exclamation sentence so called Nida’, which contains two major components that build the verse of interjection or custom Nida’ and the called or munadi. Verse in the Quran calls addressed to someone called the variation range of the pronouncement. Appeal to the Prophet Muhammad identified using five forms of words addressed to him. Thus, the study aims to analyze and evaluate the influence of context on the use of two variations of words munadi Prophet Muhammad al-Rasul al-Nabiy. Previous Islamic scholars have explained the importance of context in the interpretation of the verses of the Quran. Thus, the context of the situation to be a key aspect of the question of the use of the pronouncement of the Prophet Muhammad’s munadi. The samples were analyzed by exclamation sentences Social Semiotics Theory Halliday (1978). The findings show that the use of two forms of utterance variation munadi Prophet Muhammad studied, influenced by the context, especially by issues in the field of discourse. While as many discourses as a side effect of its use. Ayat seruan merupakan salah satu gaya bahasa yang digunakan dalam al-Quran. Dalam bahasa Arab ayat seruan dikenali sebagai ayat Nidaâ€™, yang mengandungi dua komponen utama yang membina ayat tersebut iaitu kata seru atau adat Nidaâ€™ dan orang yang diseru atau munada. Ayat seruan dalam al-Quran ditujukan kepada seseorang yang diseru menggunakan variasi dan pelbagai lafaz. Seruan kepada Nabi Muhammad SAW dikenalpasti menggunakan lima bentuk variasi lafaz yang ditujukan kepada baginda. Justeru, kajian bertujuan untuk menganalisis dan menilai pengaruh konteks situasi terhadap penggunaan dua variasi lafaz munada Nabi Muhammad SAW iaitu al-Rasul dan al-Nabiy. Sarjana Islam terdahulu telah menjelaskan berkenaan kepentingan konteks situasi dalam pentafsiran ayat-ayat al-Quran. Oleh itu, konteks situasi menjadi aspek utama dalam menjelaskan persoalan penggunaan variasi lafaz munada Nabi Muhammad SAW ini. Sampel kajian ayat seruan dianalisis berdasarkan Teori Semiotik Sosial Halliday (1978). Dapatan kajian menunjukkan penggunaan dua bentuk variasi lafaz munada Nabi Muhammad SAW yang dikaji, dipengaruhi oleh aspek konteks situasi terutamanya oleh isu dalamÂ unsur medan wacana. Manakala pelibat wacana sebagai unsur sampingan yang mempengaruhi penggunaannya.Â